Les inscriptions du mithraeum d’Angers-Iuliomagus (Maine-et-Loire) : nouvelles données sur le culte de Mithra - Michel Molin; Jean Brodeur; Maxime Mortreau (Gallia)
The preventive excavation conducted by Inrap archaeologists and led by J. Brodeur on the former Saint-Louis clinic site, in the area of Saint-Laud station, from November 2009 to September 2010, uncovered the remains of an isolated settlement next to the public road of the ancient area, built in the first years AD. They also discovered some ex voto dedicated to Mithra, written on ceramic, including a Déchelette 72 vase, found in a domus filled-in cellar. These are proof that a Mithra cult was practised before the late 2nd c. AD in a first mithraeum whose remains are badly preserved. In the middle of the 3rd c. AD, they could identify an overall rebuilding, with the discovery of several carved fragments from a spelaeum whose plan and setting were stereotyped. Its different levels of occupancy revealed characteristic remains from Mithrian banquets, including, among the animals remains, a majority of rooster parts. This cult, unexpected in this area of Gaul, has been practised from the last quarter of 2nd c. to the early 5th c. AD, when the mithraeum seems to have been deliberately and brutally destroyed. The epigraphic objects excavated in context, not in reuse, except from two of them, includes eight short inscriptions from which seven are related to the Mithra cult. They give invaluable information about the followers of this god who was, until now, unknown in this occidental area of Gallia Lugdunensis.